Why are IPOs underpriced? Evidence from Japan's hybrid auction-method offerings - Frank Kerins; Kenji Kutsuna; Richard L. Smith (Claremont McKenna College, Department of Economics, 2005)
Until October 1997, firms wishing to go public in Japan were required to use a hybrid auction process where up to half of the issue (the auction tranche) was offered to investors via a discriminatory auction. Remaining shares (the public offer tranche) were sold a few days later by a firm commitment at a fixed price. We document underpricing and partial adjustment of IPO public offer prices in Japan's auction regime, a regime where: investors are symmetrically informed or information differences are not important; roadshows are not held; preferential allocations to any investor are negligible; and institutional investing is low. The results raise important questions about theoretical interpretations of IPO underpricing in the U.S. We consider a broad range of competing, but non-mutually-exclusive, hypotheses about the reasons for underpricing and partial adjustment. Japan's auction-method evidence is most consistent with a quasicontractual allocation of risk related to initial mispricing. The risk allocation hypothesis is that, in exchange for guaranteeing a minimum price to the issuer, the underwriter participates indirectly in upside performance. The underwriter benefits from underpricing because underpriced IPOs are easier to place and because the underwriter can allocate small positions in the underpriced shares to preferred customers in implicit exchange for other benefits. As average underpricing in our sample is about three times as great as the underwriter's fee, and as some IPOs are severely underpriced, we cannot exclude the possibility that underpricing is affected by agency cost and prospect theory considerations similar to those suggested by Ritter and Welch (2002) in their review of the U.S. IPO market.
Keywords: G15; G24; G28; 330; IPO; public offering; book building; underpricing; partial adjustment